2022
DOI: 10.1155/2022/8456677
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Efficacy and Safety of Radical Resection of Rectal Cancer Combined with Selective Lateral Lymph Node Dissection in the Treatment of Low Rectal Cancer under Meta‐analysis

Abstract: Rectal cancer mostly occurs in the middle and low position in China, and many anatomical evidence has confirmed that Lateral Lymph Node Metastasis (LLNM) exists in middle and low rectal cancer. Laparoscopic surgery can penetrate into the pelvic cavity and magnify and narrow the visual field, which is helpful for lymph node dissection and vascular nerve protection, while it has minimally invasive characteristics and is considered to be more suitable for LLND. Relevant articles published from January 2000 to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%